Pengaruh Lingkungan Sekolah terhadap Motivasi Belajar Siswa MTs NW Selebung - Ahmad Jalaluddin (Aslamiah : Jurnal Pendidikan, Ekonomi, Sosial dan Budaya, 2024)
This study aims to determine the significant influence of the school environment on student motivation MTs NW Selebung. The research design used in this study is associative causal (causal), associative causal research is a type of research that aims to determine the relationship of a variable to other variables. Data collection techniques used were observation, questionnaire, and interview techniques. The data analysis techniques used are validity test, reliability test, and t-test. The results of the calculation of the validity of the instrument using the SPSS product moment formula obtained the r count results in the Extraction column which is for the school environment with the results of item 1 = 0. 372, so also with the learning motivation for item 1 = 0.401, and so on, r the table for N = 3 9 with a significant level of 5% is 0.3 16, then after a comparison is done and it turns out that r count> r Table are all valid. While the reliability test results using Cronbach Alpha (SPSS formula) it is known that the school environment has an alpha of 0, 833. A variable is said to be reliable if it gives a value greater than 0.60. Based on the results of research and data analysis conducted, obtained values for hypothesis testing using SPSS t count = 1,696 with a significance level of 5% (2-tailed) = 0,000 which is t count (2-tailed) <t table which means that Ha is accepted and Ho refused. T-test, the results obtained that a value of 1.696 is greater than I t table = 1.689, with a significance value of 0.005 <0.05, which means that the hypothetical is that there is an influence of the school environment on student motivation is accepted.